Влияние дисбаланса задних ведущих колес на устойчивость автомобиля - Подригало, М. А.; Клец, Д. М.; Сальников, Р. Ю. (НТУ "ХПИ", 2015)
Определен максимально допустимый дисбаланс задних ведущих колес в зависимости от максимально допустимого угла рыскания автомобиля. Получены аналитические выражения позволяющие определять максимально допустимый по условию ограничения угла рыскания автомобиля дисбаланс задних ведущих колес. На примере автомобиля КрАЗ-6322 определено, максимально допустимый дисбаланс на колесах автомобиля. Предлагаемый метод нормирования дисбаланса задних колес автомобилей учитывает не только массу и радиус колеса, но также и геометрические размеры автомобиля и упругие характеристики шин.

The presence of driving-wheels disbalance is entailed by worsening of operating (functional) automobile properties. Wheels disbalance has the most influence on automobile stability and handling. In this work it is defined an intercommunication between the driving-wheels disbalance size and by the parameters of automobile vibrations in a road plane, caused by the indicated disbalance. Analytical expressions, relating the size of wheels disbalance with the corner of automobile prowling are obtained. At automobile motion on a highway with even coverage directing wheels can accomplish vibrations from forces arising up at wheels disbalance presence. These vibrations take place both in horizontal and in vertical planes and are fully appropriate. If wheel rotation frequency will coincide with the system own frequency, then there are resonance and vibrations amplitudes will grow to the large sizes. Researches of tires and wheels disbalance influence on the automobile dynamics are in many works. It is certain that although on automobile stability and dirigibility large influence renders the disbalance of directing forewheels, but also the disbalance of back wheels can also influence on machines dynamics and reliability.
Influence of imbalance rear drive wheels on the stability of the vehicle
Keywords: угол рыскания; радиус колеса; геометрические размеры автомобиля; упругие характеристики шин; car; imbalance; angle yaw; stability